A comparison of pediatric liver transplant anesthesia practices with new organ procurement and transplant network pediatric policy requirements: A report from the society for the advancement of transplant anesthesia and the society for pediatric anesthesia. Issue 11 (3rd May 2022) - Moguilevitch, Marina; Polaner, David M.; Mann, Glenn; Mauner, Aaron; Beagley, Britni; Hendrickse, Adrian; Stoll, William D; DeMarchi, Lorenzo; Damian, Daniela; Sridhar, Srikanth; Costandi, Andrew; Tran, Lieu; et al.
Abstract: Introduction: Organ Procurement and Transplant Network (OPTN) pediatric policies on knowledge and skill requirements for key personnel failed to address the Director of Anesthesia for Pediatric Liver Transplantation. A Joint Committee representing the Society for the Advancement of Transplant Anesthesia and Society for Pediatric Anesthesia (SPA) surveyed all pediatric anesthesia liver transplant practices to determine if practices were aligned with policies and what changes would be needed for compliance. Methods: A survey of the Director or equivalent at each program collected data about specialized knowledge and skill sets. Questions focused on (1) skill and knowledge of the Director and team, (2) requirements for appointment, (3) experience in pediatrics, and (4) characteristics of the program including the availability of pediatric resources. Results: Response rate was 73% ( n = 63). Most responding programs had a Director (67%) with certification, selection committee, and continuing education credits outlined in existing policies. Team members met similar requirements. Alternate pathways for acquiring knowledge and skill sets were identified between programs. Conclusions: Pediatric liver transplant anesthesiologists use knowledge and skill pathways that align with the new pediatric policies. We suggest that collaborative work with oversight agencies is needed to resolve high case volume requirements originally designed for adult programs. Summary: Most pediatric liver transplant anesthesiologists in the US have specialized knowledge and skills for expert care consistent with current oversight policies. Differences in pathways to acquire knowledge and skill sets were still aligned with the new policies for pediatric transplant surgeons and bylaws for the Director of Transplant Anesthesia. We conclude that minimal changes in case volume requirements to the existing Pediatric Transplant Anesthesiology Directorship criteria that authenticates the pediatric anesthesia Director's position would improve the safety of care without limiting access to transplantation.